A conformationally stable π-expanded X-type double helicene comprising dihydropyracylene units with multistage redox behavior - Bergner, John; Borstelmann, Jan; Cavinato, Luca M.; Fuenzalida Werner, Juan Pablo; Walla, Christian; Hinrichs, Heike; Schulze, Philipp; Rominger, Frank; Costa, Rubén D.; Dreuw, Andreas; Kivala, Milan (Chemistry - a European journal, 2024)
A pi-expanded X-type double [5]helicene comprising dihydropyracylene moieties was synthesized from commercially available acenaphthene. X-ray crystallographic analysis revealed the unique highly twisted structure of the compound resulting in the occurrence of two enantiomers which were separated by chiral HPLC, owing to their high conformational stability. The compound shows strongly bathochromically shifted UV/vis absorption and emission bands with small Stokes shift and considerable photoluminescence quantum yield and circular polarized luminescence response. The electrochemical studies revealed five facilitated reversible redox events, including three reductions and two oxidations, thus qualifying the compound as chiral multistage redox amphoter. The experimental findings are in line with the computational studies based on density functional theory pointing towards increased spatial extension of the frontier molecular orbitals over the polycyclic framework and a considerably narrowed HOMO-LUMO gap. An unprecedented X-type double helicene with pi-expanded polycyclic framework and exceptional conformational stability was realized and its enantiomers were successfully separated. Comprehensive spectroscopic and electrochemical studies in conjunction with theory identified the compound as a strong chiral fluorophore with 5-stage amphoteric redox behavior.image
Gesehen am 28.02.2024